Contrasting Responses of Alien and Ancient Forest Indicator Plant Species to Fragmentation Process in the Temperate Lowland Forests - Mirjana Šipek; Lado Kutnar; Aleksander Marinšek; Nina Šajna (Plants, 2022)
Fragmentation is one of the major threats to biodiversity. In a fragmented landscape, forest specialists are losing suitable forest habitats with specific site and microclimate conditions, which results in their local extinction. Conversely, the invasion of alien species is facilitated by open forest areas and increased boundaries between forest fragments and adjacent land. We studied the effect of fragmentation in terms of fragment size impact on overall plant species richness and on selected ecologically important groups’ richness, composition, and diversity. We surveyed vegetation in the interior of 47 fragments of various sizes and one unfragmented reference forest. Our results reveal that the effect of fragmentation is complex and differs for studied plant groups. Decreasing fragment size negatively affects the overall plant richness and richness of native and ancient forest indicator plants as well as their diversity, while the effect is positive for alien plants. The highest proportion of ancient forest indicator plant species and the lowest proportion of alien plants in the unfragmented forest underline the great conservation value of forest fragments. At the same time, our results reveal that large and diverse forest ecosystems are susceptible to biological invasions as well.